Differential adherence to peer and nurse components of a supportive care package—The appeal of peer support may be related to women's health and psychological status. Issue 3 (March 2022) - Gough, Karla; Pascoe, Michaela C.; Bergin, Rebecca; Drosdowsky, Allison; Schofield, Penelope
Highlights: Adherence to nurse consultations was higher than adherence to peer consultations. Adherence to nurse sessions did not vary based on pre-radiotherapy patient factors. Adherence to peer sessions varied based on pre-radiotherapy distress and wellbeing. The appeal of peer support may be related to levels of distress and wellbeing. Abstract: Objective: Knowledge of factors associated with intervention non-adherence may provide insights into the clinical utility of non-pharmacologic interventions. Methods: This study compared complete and incomplete adherers to two separate components of a novel intervention package for women undergoing curative intent radiotherapy for gynaecological cancer on socio-demographic, clinical and pre-radiotherapy patient-reported outcomes data. Results: Adherence to the tailored specialist nurse consultations was satisfactory (71% participated in all available sessions, 19% participated in all but one). Adherence to the telephone peer support sessions was less satisfactory (47% participated in all available sessions, 24% participated in all but one session). Complete adherers to the peer sessions reported significantly lower levels of psychological distress and significantly higher levels of physical, emotional and functional wellbeing before radiotherapy. No other statistically significant differences were observed between complete and incomplete adherers to the nurse- or peer-led sessions. Conclusion: Women's ability or motivation to engage with peer support may be influenced by their health and psychological status. Further, the extent of intervention non-adherence to the peer-led component may have compromised the assessment of its efficacy. Practice implications: Peer support may be less acceptable or appropriate for women with more complex care needs. Such women may prefer specialised care from trained professionals.